Why Are We Doing Math in English Class? Building Quantitative Literacy to Improve Expository Text Comprehension - Ellen C. Agnello (Numeracy, 2018)
In 2009, The Common Core Standards shifted the English language arts focus from narrative to expository text, arguing that most texts read in college and workforce training programs are informational. By the time students are in twelfth grade, they are expected to read informational text 70% of the time. This can be challenging for English teachers if their students lack the skills needed to navigate the features of these more challenging texts. Graphs, tables, and charts detract from the readability of informational text when students lack quantitative literacy and numeracy skills. This article provides practical applications for teaching quantitative literacy in the language arts classroom through the execution of a writing workshop-based survey-inquiry project. The goal is that through experimentation with statistics obtained through collecting and analyzing their own sample of survey data, students will develop a more concrete understanding of statistics and become more proficient readers of complex expository texts.